Burn after Reading: Vol. 1, Miniature Manifestos for a Post/medieval Studies + Vol. 2, The Future We Want: A Collaboration - Joy, Eileen A.; Seaman, Myra; Cohen, Jeffrey Jerome (punctum books, 2014)
The essays, manifestos, rants, screeds, pleas, soliloquies, telegrams, broadsides, eulogies, songs, harangues, confessions, laments, and acts of poetic terrorism in these two volumes - which collectively form an academic "rave" - were culled, with some later additions, from roundtable sessions at the International Congress on Medieval Studies in 2012 and 2013, organized by postmedieval: a journal for medieval cultural studies and the BABEL Working Group ("Burn After Reading: Miniature Manifestos for a Post/medieval Studies," "Fuck This: On Letting Go," and "Fuck Me: On Never Letting Go") and George Washington University's Medieval and Early Modern Studies Institute ("The Future We Want: A Collaboration"), respectively. Gathering together a rowdy multiplicity of voices from within medieval and early modern studies, these two volumes seek to extend and intensify a conversation about how to shape premodern studies, and also the humanities, in the years ahead. Authors in both volumes, in various ways, lay claim to the act(s) of manifesting, and also anti-manifesting, as a collective endeavor that works on behalf of the future without laying any belligerent claims upon it, where we might craft new spaces for the University-at-large, which is also a University that wanders, that is never just somewhere, dwelling in the partitive - of a particular place - but rather, seeks to be everywhere, always on the move, pandemic, uncontainable, and always to-come, while also being present/between us (manifest). This is not a book, but a blueprint. It is also an ephemeral gathering in the present tense.